Natural mercury enrichment in a minerogenic fen: evaluation of sources and processes - Franzen, Carola; Kilian, Rolf; Biester, Harald (Journal of environmental monitoring, 2004)
Mercury (Hg) records in natural archives such as peat bogs are often used to evaluate anthropogenic or climatic influences on atmospheric Hg deposition. In this context, there is an ongoing discussion about natural sources or processes of Hg enrichment in natural archives. In the present study we estimated Hg fluxes from rock weathering, direct atmospheric deposition and from indirect atmospheric deposition in the catchment of a pristine minerogenic fen (GC2) located in the Magellanic Moorlands, southernmost Chile. The Hg record in the bog covers 11 174 cal. 14C years and shows Hg concentrations of up to 570 µg kg−1 with an average of 268 µg kg−1. Hg was found to be enriched in the peat by a factor of 81 if compared to the mean Hg concentrations in the rocks of the catchment (3.2 µg kg−1). Hg and also Pb, Fe, and As were found to be enriched predominately in goethite layers indicating high retention of these elements in the bog by iron oxyhydrates. It could also be demonstrated that the high peat decomposition rates in minerogenic bogs can increase the Hg concentrations in the minerogenic peat by a factor of approximately 2 at the same atmospheric Hg deposition rate if compared to ombrotrophic sites. This study has shown that Hg in minerogenic peat can be naturally enriched especially through the retention by autochthonous formed goethite and can be a solely internal process which does not require increased external Hg fluxes.